SENYAWA METABOLIT SEKUNDER KAPANG ENDOFIT TP6 DAN TPL2 YANG DIISOLASI DARI TUMBUHAN PESISIR TERONG PUNGO (Solanum sp.) - Nabila Ukhty; Kustiariyah Tarman; Iriani Setyaningsih (Universitas Teuku Umar, 2015)
Secondary metabolites, are produced naturally and serve survival functions for the organisms that producing them. Endophytic fungi is the one of microorganism has a role in producing the secondary metabolites. Endophytic fungi TP6 and TPL2 isolated from coastal plant terong pungo (Solanum sp.). Endophytic fungi TP6 and TPL2 have secondary metabolite, including alcaloid, flavonoid, phenol hidrocuinon, and terpenoid compounds.